Supplement I: Index to the Works Listed in the Working Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Related Works - Roufs, Timothy G (University of Minnesota, Duluth, 1983)
There is no page I-1 in the original physical document; the pages go directly from I-ii to I-2. The "Working Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Related Works" can be found by clicking the link under "Related to" in this record. This supplement indexes the Workinp Bibliography of Chippewa/Ojibwa/Anishinabe and Selected Works, compiled by Timothy G. Roufs (Duluth, MN: Lake Superior Basin Studies Center, 1981, and Revised Edition, 1982).